It will never happen to me : growing up with addiction as youngsters, adolescents, and adults - Black, Claudia (Central Recovery Press, 2020)
"Claudia Black's bestselling classic on the experience and legacy of being raised in an addictive household. In an all too familiar scenario, played out in millions of homes every day, children who grow up in addictive families abide by certain rules: don't talk, don't trust, don't feel. The rigid survival roles and youthful coping behaviors they take on, such as the responsible child, the adjuster, the placater, and the acting-out child can eventually contribute to problems of depression, loneliness, and addiction in adulthood. Using poignant personal stories, thoughtful explanations, and helpful exercises, Black helps readers gain personal insights and develop new skills that lead to a healthier, happier, more fulfilling life. While continuing to recognize alcohol as the primary addiction within families, this newly revised edition of It Will Never Happen to Me, which has sold more than two million copies, broadens concepts to include addictive disorders involving other drugs, money, food, sex, and work."--Publishers description.